2007
DOI: 10.1152/ajpgi.00210.2006
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen rapidly modulates mustard oil-induced visceral hypersensitivity in conscious female rats: a role of CREB phosphorylation in spinal dorsal horn neurons

Abstract: rapidly modulates mustard oil-induced visceral hypersensitivity in conscious female rats: a role of CREB phosphorylation in spinal dorsal horn neurons. Am J Physiol Gastrointest Liver Physiol 292: G438 -G446, 2007. First published September 14, 2006; doi:10.1152/ajpgi.00210.2006.-This study investigated the effect of sex hormones on mustard oil (MO)-induced visceral hypersensitivity in female rats and analyzed possible involved signaling pathways. Female rats, either intact or ovariectomized (OVX), were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…An interaction between female gonadal hormones and increased extracellular serotonin could be the key factor responsible for visceral hypersensitivity in female SERT KO rats. In a rat model of colonic inflammation‐induced visceral hypersensitivity, ovariectomy reduces, while estrogen treatment of ovariectomized rats restores visceral hypersensitivity . This effect occurred within 2 h of estrogen treatment, suggesting that it was mediated by non‐genomic mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…An interaction between female gonadal hormones and increased extracellular serotonin could be the key factor responsible for visceral hypersensitivity in female SERT KO rats. In a rat model of colonic inflammation‐induced visceral hypersensitivity, ovariectomy reduces, while estrogen treatment of ovariectomized rats restores visceral hypersensitivity . This effect occurred within 2 h of estrogen treatment, suggesting that it was mediated by non‐genomic mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…S ex hormones are reported to be important in animal models in the modulation of "visceral hypersensitivity" (VH), a defining factor in pathogenesis of irritable bowel syndrome (IBS). However, the VH models in these reports were mainly secondary to severe colonic mucosal inflammation, 1,2 which is not observed in IBS patients. Therefore, the role of estrogen in the VH model in the absence of mucosal inflammation should be examined.…”
mentioning
confidence: 88%
“…7 For example, we have shown that estrogen can restore mustard oil-induced VH in ovariectomized (OVX) rats in 90 minutes. 2 Others have demonstrated that a single injection of estrogen can rapidly phosphorylate CREB in gonadotropin-releasing neurons in OVX mice within only 15 minutes, and this effect can persist for 4 hours. 9 A G-protein-coupled receptor, GPR30 (an alternative to the classical ERs), has recently been identified to be involved in the rapid action of estrogen through its direct association with estrogen.…”
mentioning
confidence: 99%
“…There are several models that induce colonic or bladder hypersensitivity lasting from hours to weeks in the absence or presence of inflammation. Female hypersensitivity to colorectal distention was reported following mustard oil irritation of the colon and the magnitude of the increase was greater in females compared to males (Ji et al, 2012b; Lu et al, 2007). Similarly, hypersensitivity that persisted several weeks in the absence of colonic inflammation was greater in female rats (Bourdu et al, 2005).…”
Section: Animal Studies Supporting a Sex Difference And Hormonal Mmentioning
confidence: 99%
“…Similar to noninflamed animals, estrogen modulated the magnitude of response in females. Ovariectomy reduced the visceromotor response to intracolonic mustard oil which was restored by E2 replacement (Ji et al, 2005; Lu et al, 2007). Intracolonic 5HTP, a serotonin precursor, induced colonic hypersensitivity without noticeable inflammation that was attenuated by ovariectomy and facilitated by E2 (Lu et al, 2009).…”
Section: Animal Studies Supporting a Sex Difference And Hormonal Mmentioning
confidence: 99%